The Relationship of Husband Support with the Regularity of Pregnancy Checks - Nur Anisafauziah Ilham (Bulletin of Inspiring Developments and Achievements in Midwifery, 2024)
Pregnancy is an important period that requires attention and support, both from health workers and the immediate environment, especially the husband. Optimal husband support can affect the behavior of pregnant women in conducting regular pregnancy checks. The survey found that there was still a lack of regularity for pregnant women in conducting Antenatal examinations during pregnancy.  Objective: This study aims to determine the relationship between husband's support with the regularity of pregnancy checks in the work area of Ambacang Health Center Year 2024. Methods: this type of research is analytical with cross sectional approach. The population of the study was all pregnant women who conducted pregnancy screening in the region, with a sample of 75 people selected using purposive sampling technique. Data collection was conducted by structured questionnaires and analyzed using Chi-Square test. Results: the results showed that most of the respondents had the support of their husbands in the good category (68%) and most pregnant women had regular pregnancy checks (72%). The results of statistical tests showed a significant relationship between husband's support with the regularity of pregnancy checks (p < 0.05). Implications: the implications of this study indicate the importance of increasing the role of the husband in supporting pregnancy through family education and counseling programs in the community. Conclusion: the better the husband's support, the higher the regularity of pregnant women in conducting pregnancy checks at the Ambacang Health Center.